Effect of daily morphine administration and its discontinuation on delay discounting of food in rhesus monkeys. Issue 2 (April 2016) - Maguire, David R.; Gerak, Lisa R.; France, Charles P.
Abstract : Opioid abusers discount delayed reinforcers more rapidly than nonusers; however, it is unclear whether chronic drug administration or its discontinuation impacts discounting. This study examined the impact of daily morphine administration and its discontinuation on delay discounting of food in rhesus monkeys. Responding on one lever delivered one food pellet immediately; responding on another lever delivered two food pellets either immediately or after a delay (30–120 s) that increased within the session. Monkeys ( n =3) responded for the large reinforcer when both reinforcers were delivered immediately and more for the smaller, immediately available reinforcer as the delay to delivery of the large reinforcer increased. When administered acutely, morphine (0.032–5.6 mg/kg) increased trial omissions and had variable effects on choice, with small doses decreasing and large doses increasing choice of the large delayed reinforcer. Chronic morphine administration (0.1 mg/kg/day to 3.2 mg/kg twice daily) reduced choice of the large delayed reinforcer in two monkeys, while increasing choice in a third monkey. Despite the development of tolerance to some effects (i.e. rightward shifts in dose–effect curves for the number of trials omitted) and evidence of mild opioid dependence (e.g. decrease in the number of trials completed, as well as body weight), discontinuation of treatment did not appear to systematically impact discounting. Overall, these results suggest that repeated opioid administration causes persistent effects on choice under a delay discounting procedure; however, differences in the direction of effect among individuals suggest that factors other than, or in addition to, changes in discounting might play a role.